How art made the world (BBC Worldwide, 2005)
"Discovering how the first big artistic discoveries were made, and how they have cascaded down the centureis to define the look of the present day - this is your invitation to see the wonder of an utterly non perspective. Encompassing everything from cave paints to ceramics and pyramids to palaces, the series probes the global trend for unrealistic depictions of the human body; The secret powers of the future films; how politicians manage to manipulate people so easily; visions of death and the afterlife; and why we use imagery at all". - Περίληψη από το κιβώτιο